ОПТИМІЗАЦІЯ СТРУКТУРНИХ ВУЗЛІВ МАГНІТНО-НАПІВПРОВІДНИКОВИХ ГЕНЕРАТОРІВ ІМПУЛЬСІВ - Волков, I.В.; Зозульов, В.І.; Голубєв, В.В.; Пащенко, В. В.; Сторожук, А.І. (Інститут електродинаміки Національної академії наук України, 2019)
The new scientific results, obtained on the basis of complex research and optimization of structural units of magnetic - semiconductor pulse generators (MSPG) of micro and nanosecond ranges, are presented. Two types of DC / DC converters, focused on their application with high efficiency in MSPG and other devices of power electronics were investigated. Practical schemes of combined single-phase power rectifiers have been developed. It is proved that these rectifiers have the widest range of output voltages - within ~ (300 ... 600) V and the choice of external characteristics that are optimal for different loads. It has been shown that the spin-use of the considered DC / DC converters and combined rectifiers as the input part of the MSPG most favor the increase the efficiency of MSPG. New types of transistor switches with four electrodes, effective for application not only in MSPG, but also in many devices of power electronics, are offered. References 11, figures 9, tables 3.